KONTRIBUSI SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN MAMUJU - YUSUF, SUPRIYADI (LPPM Universitas Muhammadiyah Mamuju, 2023)
This research uses quantitative data analysis, which is a form of data analysis that uses numerical categories, thus the data must be clarified in certain categories using nominal values. There are two temporary answers which are the subject of discussion in this research which have been tested using statistical analysis methods. Based on the results of data analysis it can be concluded that: (a). The contribution of tourism sector income to Mamuju Regency's original regional income occurred in 2021 and 2022, with a contribution value of 0.02%. The highest contribution occurred in 2018, with a contribution value of 0.08%. From the total local original income, it can be concluded that in the time period studied, the Mamuju Regency government has not been able to rely on tourism sector income as the leading factor in making up local original income. (b). The highest income effectiveness of the Mamuju Regency Tourism Sector occurred in 2018 with a value of 66.03%. Meanwhile, the lowest effectiveness occurred in 2022 with a value of 9.32%. Tourism sector income is included in the less effective category because realized income does not exceed the target of 100%.